Communities and law : politics and cultures of legal identities - Barzilai, Gad (University of Michigan Press, 2003)
Offers an alternative approach to liberalism and to communitarianism, with an empirical focus on Israel.
Keywords: Law -- Social aspects -- Israel.; Minorities -- Legal status, laws, etc. -- Israel.; Droit -- Aspect social -- Israël.; Minorités -- Droit -- Israël.; LAW -- Jurisprudence.; LAW -- General Practice.; LAW -- Reference.; LAW -- Essays.; LAW -- Paralegals & Paralegalism.; LAW -- Practical Guides.; POLITICAL SCIENCE -- Civics & Citizenship.; Law -- Social aspects; Minorities -- Legal status, laws, etc.; Israel; Minderheden.; Recht.; Cultuur.